LEED's Contribution to the United Nations' Sustainable Development Goals. Issue 1 (1st May 2022) - Goubran, S; Walker, T; Cucuzzella, C; Schwartz, T
Abstract: Green and sustainable building standards strongly influence sustainable building activities. Therefore, it is essential to assess how current standards contribute to achieving the United Nations' Sustainable Development Goals (SDGs). A comprehensive catalogue is developed, and the analysis of overlaps between the standard and the SDGs is automated through direct content analysis. LEED V4.1 BD+C for New Construction is selected as the leading green building standard globally. Similar to previous work, LEED generates matches with eight SDGs – SDG3 (health), SDG12 (sustainable consumption and production), SDG 11 (sustainable cities) being the highest-ranked, respectively This content analysis is complemented with a qualitative analysis founded on innovation and risk-management theory, to assess the transformative capacity of the standard. The findings indicate that only about 6% of LEED's score calls for positive value creation and transformative change, with most of its credits directed towards the management and reduction of known building instigated environmental risks. The research concludes that while there are overlaps between the LEED credits and the SDGs' topics, further research is needed to validate its contribution to realizing the 2030 Agenda empirically.